2019
DOI: 10.3390/foods8060194
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Effect and Probiotic Potential of Phage Resistant Lactobacillus plantarum and its Interactions with Zoonotic Bacterial Pathogens

Abstract: Development of phage-resistant probiotic particularly Lactobacillus is an alternative approach to enhance their beneficial effects as in animal feed supplements. In this study, we developed phage-resistant Lactobacillus plantarum (LP+PR) mutant and compared their antimicrobial effects and probiotic potential against zoonotic bacterial pathogens including Salmonella enterica serovar Typhimurium, enterohemorrhagic Escherichia coli (EHEC), Staphylococcus aureus, and Listeria monocytogenes with phage-sensitive L. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 43 publications
(47 reference statements)
1
6
0
Order By: Relevance
“…and Bifidobacterium spp., it seems, in fact, that strains in co-cultures may produce short chain fatty acid and other active metabolites in varying proportions, showing a synergic effect [39]. Moreover, the results confirmed the effects of the strains B. longum BB536 and L. rhamnosus HN001 used in combination to act against the bacterial clinical isolates in order to impede the adhesion to the HT-29 human intestinal cell line; other studies present in the literature demonstrated that the production of antimicrobial compounds by probiotic strains contribute to inhibit the adhesion of pathogenic bacteria [6,35,39]. The very strong inhibitory activity observed for the acid supernatants aBB536-CFS and aHN001-CFS against some reference strains and clinical isolates could be due to the combination of the effect of different metabolites such as lactic acid, acetic acid, small peptides and bacteriocins released in the supernatant by the producing strains.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…and Bifidobacterium spp., it seems, in fact, that strains in co-cultures may produce short chain fatty acid and other active metabolites in varying proportions, showing a synergic effect [39]. Moreover, the results confirmed the effects of the strains B. longum BB536 and L. rhamnosus HN001 used in combination to act against the bacterial clinical isolates in order to impede the adhesion to the HT-29 human intestinal cell line; other studies present in the literature demonstrated that the production of antimicrobial compounds by probiotic strains contribute to inhibit the adhesion of pathogenic bacteria [6,35,39]. The very strong inhibitory activity observed for the acid supernatants aBB536-CFS and aHN001-CFS against some reference strains and clinical isolates could be due to the combination of the effect of different metabolites such as lactic acid, acetic acid, small peptides and bacteriocins released in the supernatant by the producing strains.…”
Section: Discussionsupporting
confidence: 70%
“…Imbalance between the microbial populations belonging to the main phyla distributed in the adult human gut has been documented in patients with gastrointestinal and urinary infections [11, 16, 17, 18, 19, 20, 21, 22, 23, 34]. Several studies have demonstrated that bifidobacteria and Lactic Acid Bacteria (LAB) are able to competitively exclude pathogenic bacteria and yeasts, either directly, through interactions with pathogenic strains, or indirectly, through the production of active metabolites and the induction of host immune defense [33, 35]. Probiotics could, therefore, represent a potential alternative to conventional antimicrobials either as prophylaxis or as treatment of gastrointestinal infections and for these reasons they remain one of the main means to contrast these infections [33, 36].…”
Section: Discussionmentioning
confidence: 99%
“…Our findings showed that the CFS of L. reuteri and L. plantarum had a more powerful effect than the CFS of L. fermentum on gene expression. Previous researches suggested that human probiotic isolates, such as L. plantarum, inhibited bacterial virulence, inhibited bacterial virulence, representing a promising alternative to antibiotic prophylaxis of staphylococcal menstrual TSS and potentially of other S .aureus-mediated diseases (40,44). Though the actual physiological function of supernatant compounds is unclear, these compounds may serve signaling molecules involved in host-bacterial interactions, considering their biological effects in humans (39,45).…”
Section: Discussionmentioning
confidence: 99%
“…e in vivo and in vitro analysis proposed that intestinal microorganisms and metabolites may affect the development of the central nervous system (CNS) and regulate the stress responses and neural circuitry [66]. e murine model of infection has been studied for understanding the mechanism and immune-regulatory effects of [100,101] (ii) Genetically stable (iii) Stability and viability of the desired probiotic features during the preparation till the distribution of probiotic products (iv) High rates of survival in finished products during storage (in microaerophilic and aerobic conditions) (v) Large-scale production (vi) Desired sensory properties Functionality (i) Documented and validated health effects (i) Sensitivity to enzymes and bile salts [102] (ii) Adhesion to the mucosal lining (ii) Susceptibility to low pH in the host stomach (iii) Competitive in terms of its interaction with intestinal microbiota (iii) Sensitivity to bacteriocins and acids produced by gut microflora (iv) Ability to grow at the target site and maintain the metabolic properties Physiological conditions (i) Immunomodulation (i) Mutagenesis [102] (ii) Cholesterol metabolism (ii) Carcinogenesis (iii) Lactose metabolism (iv) Antagonistic activity towards pathogenic microbes (e.g., Salmonella species, Helicobacter pylori, Clostridium difficile, and Listeria monocytogenes)…”
Section: Cognitive Healthmentioning
confidence: 99%